Psychometric and biohormonal indices of dental anxiety in children. A prospective cohort study. (July 2014) - Yfanti, Konstantina; Kitraki, Efthymia; Emmanouil, Dimitris; Pandis, Nikolaos; Papagiannoulis, Lisa
Abstract The stress of dental treatment often elicits negative emotions in children, expressed as dental fear or anxiety. Highly anxious children obstruct treatment and avoid therapy, further amplifying oral health problems. The aim of this study was to examine the neuroendocrine and autonomic nervous system responses to dental treatment and their possible interactions and associations with psychometric indices of anxiety, caries, previous dental experience, anesthesia, age and gender in school children. Upon informed consent, saliva was obtained from 97 children (59% males, mean age ± SD: 89.73 ± 15 months) in the Clinic of pediatric dentistry before treatment, immediately post-treatment and at the recall visit to determine cortisol and salivary alpha-amylase (sAA) levels. Dental and general anxiety was assessed through specific questionnaires completed by the children. Compared to pre-treatment, cortisol levels were increased following treatment, while sAA levels were higher at the recall. Pre- and post-treatment cortisol and sAA responses were positively correlated. Dental and general anxiety questionnaire scores were also significantly correlated with each other. The integrated autonomic and neuroendocrine responses prior to treatment were correlated with state anxiety and those following treatment with dental anxiety. However, univariable and multivariable linear regression analysis associated post-treatment cortisol, but not sAA, levels with dental anxiety. No associations of cortisol or sAA responses with caries, age, gender, previous dental experience or anesthesia were detected. These data provide some evidence that both sAA and cortisol levels are altered in children in anticipation or during dental treatment, but only cortisol levels are associated to dental anxiety.